Widespread vertical transmission and associated host sex-ratio distortion within the eukaryotic phylum Microspora. - Terry, Rebecca S. (2004)
Vertical transmission (VT) and associated manipulation of host reproduction are widely reported among prokaryotic endosymbionts. Here, we present evidence for widespread use of VT and associated sex-ratio distortion in a eukaryotic phylum. The Microspora are an unusual and diverse group of eukaryotic parasites that infect all animal phyla. Following our initial description of a microsporidian that feminizes its crustacean host, we survey the diversity and distribution of VT within the Microspora. We find that vertically transmitted microsporidia are ubiquitous in the amphipod hosts sampled and that they are also diverse, with 11 species of microsporidia detected within 16 host species. We found that infections were more common in females than males, suggesting that host sex-ratio distortion occurs in five out of eight parasite species tested. Phylogenetic reconstruction demonstrates that VT occurs in all major lineages of the phylum Microspora and that sex-ratio distorters are found on multiple branches of the phylogenetic tree. We propose that VT is either an ancestral trait or evolves with peculiar frequency in this phylum. If the association observed here between VT and host sex-ratio distortion holds true across other host taxa, these eukaryotic parasites may join the bacterial endosymbionts in their importance as sex-ratio distorters.